Pendidikan Rahmah Dalam Perspektif Al-Qur'an: (Kajian secara teoristis dan aplikatif untuk pendidikan di Indonesia) - Sumarno, Sumarno (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
The education is the change process of human behavior for the better (change behavior). To achieve success in the educational process of course there is a special strategy to be done by the teacher. In this discussion the author offers a solution that to achieve the success of teacher education should be taught with a model of Rahmah (compassion). In this discussion of the methods used is literature review with library research or study approach to librarianship. To produce good writing then carefully study held a writer on literatures relating to education to rahmah who are sourced in the Qur’an, books, journals, papers and other articles. As for the conclusion in this discussion is; First, education in the Islamic discourse is more popular with the term tarbiyah, meaning associated with the word Lord (God). Second, God introduces him self as the education that has compassion. Third, implementation of rahmah in education, teachers should love his students as his own son. When teaching using the sympathetic way, smooth, and not use violence, diatribe, invective, and so on. Fourth, rahmah education raises the secure attachment on the students thus creating positive relationship between teacher-students. Positive relationship can cause positive emotions.